Utilization of Maternal Health Care Services among Mothers Residing at Slum Area - Shrestha, Shreemaya; Shrestha, Dev Kumari (Journal of Nepal Health Research Council, 2019)
Background: Appropriate utilization of maternal health care services is very important tool to reduce the maternal and child morbidity and mortality rate. This study was conducted to assess the utilization of maternal health care services by the women for their last pregnancy in one year period and to find out it’s association with selected variables.Methods: Descriptive cross sectional study was conducted for one year by using semi-structured questionnaire among 285 mothers residing at slums area of Dharan sub-metropolitan city after taking written consent from them. Ethical clearance was obtained from Institutional Review Committee, BPKIHS and Dharan Sub-metropolitan city office. Simple random sampling followed by snowball sampling method was used to collect the data by interview method.Results: Majority (95.1%) had one Antenatal visit, 60.4% had initiated antenatal visit at first trimester and 78.99% had completed 4 or more antenatal visits. Only 35.8% had taken complete dose of iron and calcium. Majority 262 (91.92%) respondents have taken Tetanus Toxoid immunization and among them only 74.42% had taken 2 dose of TT injection. Women who delivered in health facility accounted for 70.9% but only 28.8% went for postnatal visit. Majority (65.3%) received health advice during postnatal period. Nearly 40% respondents used family planning after post partum period .There was significant association between utilization of antenatal and delivery services with Educational status of respondents and their husbands and number of pregnancy and between utilization of postnatal services with occupation of husband.Conclusions: Utilization of maternal health care services, antenatal services utilization were satisfactory whereas postnatal services and family planning services utilization were very poor. Utilization of maternal health services should be encouraged by conducting public awareness programmes.Keywords: Maternal health services; utilization; women.